(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the outcome of status epilepticus in patients admitted with seizure in tertiary care hospital. Study Design: Cross sectional study Place and Duration of Study: This study conducted at the LGH & JPMC, Karachi from January 2016 to October 2016. Materials and Methods: Total 108 patients included in the study after informed consent in written form. Patients included in the study who fulfill the inclusion criteria. Data was collected in preform proforma in 108 cases following the selection criteria. Patients were recruited after informed consent of the patients and ethical approval from the institution. The patients were followed till discharge and all the information collected in preformed proforma.Standard protocol followed for the treatment of status epilepticus. Outcome measured in the form of fully recovered, recovered with neurological deficit & death. The data were analyzed on version 17. Descriptive statistics was used to summarize the categorical variables such as gender, history of epilepsy, status epileptic in past, drug withdrawal, febrile illness, mortality presented as frequencies and percentages while continuous variable like age was presented as Mean ± SD. Chi-square test p-value ≤ 0.05 was taken as significant. Results: Among 108 patients 60(56.6%) were male & 48(44.4%) were female, mean age of study group were 31.3 + -13.5 years. The results found that only 2 (1.9%) patients were expired (p < 0.01) while 106 patients fully recovered without any neurological deficit. Conclusion: We concluded after this study that early recognition & prompt treatment of the epileptic patients in status epilticus have better outcome.